ANDROID-BASED LEARNING MEDIA ON STUDENTS' LEARNING OUTCOMES ON THERMOCYMIA MATERIALS - Ramlan Silaban; Freddy Tua Musa Panggabean; Hendra Simanjuntak; David Frans Pardamean Sihombing (Jurnal Ilmu Pendidikan Indonesia, 2022)
The purpose of this study was to determine: (1) the effectiveness of Android-based learning media on student learning outcomes in thermochemical material; (2) Student responses to the use of Android-based learning media on thermochemical material; (3) The learning outcomes of students who are taught using Android-based chemistry learning media are the same as the KKM value. This research was conducted at Public High School 5 Medan with a total sample of 68 people. The research instrument consisted of standardized tests and questionnaires. The analytical techniques used are: (1) Two-party t test (Independent Samples T test); and (2) One Sample Test. From the results of this study, it was found that: (1) Anroid-based chemistry learning media was effective on student learning outcomes on thermochemical material, with a t-test of 7.063 which was greater than t-table of 2.00. Then based on the Gain Score, the t-test of 6.843 was obtained, which was greater than the t-table of 2.00; (2) Student responses "Very Interesting" with percentages of 92.27%, 93.93% and 92.12%, respectively, on the use of anroid-based learning media in thermochemical material; (3) The learning outcomes of students who are taught using android-based chemistry learning media are not the same as the KKM value, where , tcount (2.126) > ttable (2.032), means that it has a positive effect on KKM